Occasionally Binding Constraints in the New Keynesian Model: Solution by Time Iteration - Mendes, V.; Mendes, D. A. (JuliaCon2019, 2019)
In this paper we solve a New Keynesian Model with a typical Taylor Rule for monetary policy, and with occasionally binding constraints (OBCs) on nominal interest rates. We consider two dierent states (a ”normal” state and the ”Zero Lower Bound” on interest rates), modelled as a Markov process. The solution is obtained by the method of time iteration and follows the approach presented by Sunakawa (2019). Surprisingly, the method ends up being extremely easy to implement (with less than 200 lines of code), flexible, and extremely fast.